2015
DOI: 10.1016/j.jsv.2014.12.043
|View full text |Cite
|
Sign up to set email alerts
|

In-plane vibrations of a rectangular plate: Plane wave expansion modelling and experiment

Abstract: Theoretical and experimental results for in-plane vibrations of a uniform rectangular plate with free boundary conditions are obtained. The experimental setup uses electromagnetic-acoustic transducers and a vector network analyzer. The theoretical calculations were obtained using the plane wave expansion method applied to the in-plane thin plate vibration theory. The agreement between theory and experiment is excellent for the lower 95 modes covering a very wide frequency range from DC to 20 kHz. Some measured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This is because of the blurring function produced when there is a spherical aberration and because of the phase of coherent illumination. From Figures-(11) and (12), found that MTF becomes narrower (bad optical imaging system) under the effect of spherical aberration, especially in the case of coherent illumination and small aperture. This is because of the blurring function produced when there is a spherical aberration and because of the phase of coherent illumination.…”
Section: Numeric Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is because of the blurring function produced when there is a spherical aberration and because of the phase of coherent illumination. From Figures-(11) and (12), found that MTF becomes narrower (bad optical imaging system) under the effect of spherical aberration, especially in the case of coherent illumination and small aperture. This is because of the blurring function produced when there is a spherical aberration and because of the phase of coherent illumination.…”
Section: Numeric Results and Discussionmentioning
confidence: 96%
“…61, No. 10, pp: 2599-2609 2601 The PSF for incoherent illumination can be represented by[1] PSF(x,y)=| | (4) while for coherent illumination PSF(x, y) = | | (The modulation transfer function (MTF) was evaluated from eqs 4 and 5 and for the two cases of illumination (coherent and incoherent)[12] MTF(x, y) = | | (6) where | | represents the Modulus of the function. FT denotes the Fourier transform and pup( , ) define the pupil function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the influence of the PC periodicity, the special frequency range between two bands that have no intersection is called the band gap, in which the elastic wave cannot propagate through the PC. The band gaps produced by PC is valuable both in theory and in practice for sound insulation 912 . According to the formation of BGs, PCs can be divided into two categories, Bragg scattering or the local resonance 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…Ritz method was used by Dozio 13 using trigonometric displacement functions to evaluate the in-plane vibration characteristics of rectangular plates with edge restraints which is considered as elastic and non-uniform in nature. The analysis of in-plane vibration of isotropic rectangular plates has also been presented in the literature using the plane wave expansion theory 14 for a free-free and a fully clamped boundary. The theoretical results have been validated using experimental analysis for a free-free plate.…”
Section: Introductionmentioning
confidence: 99%